Structural unemployment in Western Europe : reasons and remedies - Werding, Martin (CESifo seminar series., 2006)
Examines the different patterns and long-term trends behind persistent unemployment across Western Europe in light of the developments in labour market theory. This work explains the emergence and persistence of unemployment.